Qualidade do solo e percepção socioambiental de produtores e agentes rurais no cultivo de fumo em Pilões/RN - Pontes, Nadja Cristina (2016)
Environmental quality has been much discussed as a result of human awareness of the sustainable use of natural resources, although restricted conservation actions are being developed. In the panorama of environmental impacts from agriculture it is common to observe the decrease in soil quality and the difficulty of quantifying the loss of these attributes as well as the environmental partner perception of the main actors in the rural context. In view of this problem, the objective was to evaluate the chemical attributes of the soil In tobacco growing areas based on soil environmental quality index, as well as to evaluate the environmental partner impact of this activity according to the perception of farmers and rural agents of the city of Pilões/RN through semi-structured interviews. It was possible to improve the environmental quality for P, Ca, Mg and Al in relation to the native forest, unlike the changes observed for CE, pH and Al + H, which did not present favorable results for soil quality. According to the environmental partner perception of the producers and rural agents, the cultivation of tobacco has negatively altered the environment in which they live, even though these farmers know good practices for the preservation of the soil. According to the interviewees, the main dissatisfaction generated by the tobacco company installed in the municipality was the absence of contribution to the social development of Pilões, however, tobacco production represented a major source of income and job creation for the municipality of Pilões.